2008
DOI: 10.1002/cnm.1117
|View full text |Cite
|
Sign up to set email alerts
|

A 1D arterial blood flow model incorporating ventricular pressure, aortic valve and regional coronary flow using the locally conservative Galerkin (LCG) method

Abstract: SUMMARYThere is an important interaction between the pumping performance of the ventricle, arterial haemodynamics and coronary blood flow. While previous non-linear 1D models have focused only on one of these components, the model presented in this study includes coronary and systemic arterial circulations, as well as ventricular pressure and an aortic valve that opens and closes 'independently' and based on local haemodynamics. The systemic circulation is modelled as a branching network of elastic tapering ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
380
0
4

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 206 publications
(393 citation statements)
references
References 106 publications
7
380
0
4
Order By: Relevance
“…In this case a methodology based on the fact that the pressure drop between the aortic arc and the descending aorta has to be the same, regardless of the route which is followed (through the coarctation or through one of the collateral vessels), can be devised. Additionally, (13) should be used in this case, since it does not require the time-varying flow rate through the coarctation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case a methodology based on the fact that the pressure drop between the aortic arc and the descending aorta has to be the same, regardless of the route which is followed (through the coarctation or through one of the collateral vessels), can be devised. Additionally, (13) should be used in this case, since it does not require the time-varying flow rate through the coarctation.…”
Section: Resultsmentioning
confidence: 99%
“…This is done to minimize the wave reflections at the bifurcations. Under this approach, first the reflection coefficient at a bifurcation is computed 13 :…”
Section: Estimation Of Aortic Wall Parametersmentioning
confidence: 99%
“…Langewouters et al [14] performed measurements in human thoracic and abdominal aortas and found that an arc-tangent model (consistent with a quadratic variation of E with pressure) matches the experiments very well. The simple relation 5 however has been used successfully for numerical simulations of pressure wave propagation in arteries [15][16][17] and is adopted in the present work as well. Using this pressure-area relation and substituting into (4), we find that the distensibility D is given by System (3) with pressure-area relation (5) is a non-linear hyperbolic system.…”
Section: The 1d Modelmentioning
confidence: 99%
“…Using this pressure-area relation and substituting into (4), we find that the distensibility D is given by System (3) with pressure-area relation (5) is a non-linear hyperbolic system. It can be transformed into a system of (2) decoupled equations (the methodology and the intermediate steps are well described in the literature, for example [12,17]) as…”
Section: The 1d Modelmentioning
confidence: 99%
See 1 more Smart Citation